Protein Biomarkers in Saliva in Oral Squamous Cell Carcinoma - Bhattarai, Bishwa Prakash; Klongnoi, Boworn; Khovidhunkit, Siribang-on Pibooniyom; Wongsirichat, Natthamet (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2017)
Abstract Diagnosis of oral squamous cell carcinoma (OSCC) relies mainly on the histopathological analysis of the biopsied tissue which is always traumatic for the patient. Salivary biomarkers might be an important adjunct to the diagnosis of OSCC especially in early stages of the disease because of the ease and non-invasiveness of specimen collection. Many salivary biomarkers have already been introduced. This article is a review of the protein biomarkers that have been investigated for their usefulness in association to OSCC. Key Words: Oral cancer, biomarker, protein, salivary diagnostics